Modeling of unsteady natural convection for double-pipe in a partially cooled enclosure - Rahman, M. M.; Oztop, Hakan Fehmi; Mekhilef, Saad; Saidur Rahman,; Ahsan, Amimul; Al-Salem, Khaled (Taylor & Francis, 2014)
In this article, a model is developed for unsteady natural convection heat transfer and fluid flow in a partially cooled enclosure with a hollow cylinder through it. The right vertical wall of the enclosure is cooled partially. The location of the partial cooling is set up in three different configurations; namely, bottom (P 1), middle (P 2), and top (P 3). A hollow cylinder is located at the middle of the enclosure to simulate a double-pipe heat exchanger. Three values of Grashof number are applied in this work, i.e., 104, 105 and 106, and three lengths of the cooler, i.e., 0.2, 0.4 and 0.6. Finite element method was utilized to solve the unsteady dimensionless conservation equations of mass, momentum and energy. It is found that the length and location of cooler does not have a significant effect on the natural convection for the case of the low Grashof number. The maximum heat transfer rate is reached when the cooler is located at the middle of the vertical wall.